SIGNIFICANCE OF INFORMATION GAIN RATIO FOR IMPROVING CLASSIFICATION OF HEART DISEASES - R.KARTHIKEYAN; A.KUMARAVEL; V.KHANAA (International Journal of Pharma and Bio Sciences, 2015)
Mechanizing the prediction of new patients’ heart disease diagnosis based on data mining on historical data is an extremely useful tool in the cardiology stream. There exist many studies focusing on this specific aspect of the filtering the attributes. The objective of this research paper is two-fold. First, we look into four distinct classifiers for evaluating the relevancy of the attributes and we investigate the effects of feature selection in such experiments.